Предмет: Алгебра,
автор: asemaospanova2
помогите пожалуйста
Заранее спасибо
Приложения:
Ответы
Автор ответа:
0
4*4*4*4*4*4=4^6
(-3)*(-3)*(-3)*(-3)*(-3)=(-3)^5
k*k*k*k*k*k*k=k^6
(2/3)*(2/3)*(2/3)*(2/3)=(2/3)^4
(-3)*(-3)*(-3)*(-3)*(-3)=(-3)^5
k*k*k*k*k*k*k=k^6
(2/3)*(2/3)*(2/3)*(2/3)=(2/3)^4
Автор ответа:
0
1)
2)
3)
4)
2)
3)
4)
Похожие вопросы
Предмет: Другие предметы,
автор: vika2665
Предмет: Математика,
автор: Аноним
Предмет: Биология,
автор: Smoll5Smoll53
Предмет: Химия,
автор: Катяяяяр
Предмет: История,
автор: Аноним